2013
DOI: 10.1007/s10495-013-0875-x
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide transcriptional analysis of apoptosis-related genes and pathways regulated by H2AX in lung cancer A549 cells

Abstract: Histone H2AX is a novel tumor suppressor protein and plays an important role in apoptosis of cancer cells. However, the role of H2AX in lung cancer cells is unclear. The detailed mechanism and epigenetic regulation by H2AX remain elusive in cancer cells. We showed that H2AX was involved in apoptosis of lung cancer A549 cells as in other tumor cells. Knockdown of H2AX strongly suppressed apoptosis of A549 cells. We clarified the molecular mechanisms of apoptosis regulated by H2AX based on genome-wide transcript… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 27 publications
0
19
0
Order By: Relevance
“…In particular, H2AX phosphorylation at Ser139 has an important role in the apoptosis of tumor cells [24,25,27] . Hence, we investigated whether resveratrol could induce H2AX phosphorylation in CML cells.…”
Section: Resveratrol Induces H2ax Phosphorylation and Apoptosis In K5mentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, H2AX phosphorylation at Ser139 has an important role in the apoptosis of tumor cells [24,25,27] . Hence, we investigated whether resveratrol could induce H2AX phosphorylation in CML cells.…”
Section: Resveratrol Induces H2ax Phosphorylation and Apoptosis In K5mentioning
confidence: 99%
“…Apoptosis is almost completely blocked in H2AX -/-mouse embryo fibroblasts (MEFs). The transfection of H2AX-wt, but not H2AX-139m (Ser139 was mutated to block H2AX phosphorylation), into H2AX -/-MEFs restored the ability to Increasing evidence has also demonstrated that H2AX phosphorylation is involved in the apoptosis of tumor cells [23,25,27] . To investigate the important role of ÎłH2AX in the resveratrol-induced apoptosis of CML cells, we assessed the effects of H2AX overexpression and knockdown on the apoptosis of CML cells.…”
Section: H2ax Phosphorylation Is Required For the Resveratrol-inducedmentioning
confidence: 99%
“…Moreover, H2AX was shown to induce cell cycle arrest via the p53/p21 pathway (44). In addition, knockdown of H2AX was shown to strongly suppress apoptosis in lung cancer cells (45). To elucidate the biological significance of H2AX degradation through EBNA3C in LCLs as well as to explore the underlying molecular mechanism of this DNA damage protein in EBVinduced B-cell lymphomagenesis, we used H2AX knockdown LCL1 cells compared to the control vector LCL1.…”
Section: H2ax Expression Is Downregulated In the Presence Of Ebna3cmentioning
confidence: 99%
“…In the network, cycle nodes represent genes, and edges between two nodes represent interactions between genes, which are expressed by degree, where indegree represent the number of source genes of a gene and outdegree represent the number of target genes of a gene [28]. Degree measures how correlated a gene is with all other network genes.…”
Section: Resultsmentioning
confidence: 99%
“…The Signal-net analysis method was used to screen for the source gene or target gene of some gene in whole KEGG-pathway database [28]. The BC values and degrees of genes are the key attributes of a network; they show the tendency of genes to interconnect with others and were used to seek out major target genes.…”
Section: Discussionmentioning
confidence: 99%